2014
DOI: 10.1098/rspb.2013.3357
|View full text |Cite
|
Sign up to set email alerts
|

Amygdaloid and non-amygdaloid fear both influence avoidance of risky foraging in hungry rats

Abstract: Considerable evidence seems to show that emotional and reflex reactions to feared situations are mediated by the amygdala. It might therefore seem plausible to expect that amygdala-coded fear should also influence decisions when animals make choices about instrumental actions. However, there is not good evidence of this. In particular, it appears, though the literature is conflicted, that once learning is complete, the amygdala may often not be involved in instrumental avoidance behaviours. It is therefore of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Helmstetter and Fanselow [44] found that introduction of random shocks caused rats to decrease meal frequency but increase meal size such that they reduce exposure to footshocks in the foraging area while maintaining caloric intake. A recent study showed that random footshocks also caused rats to decrease pressing the lever distal to the nest, where it will take the animal longer to escape from shock, and increase pressing the lever proximal to the nest, where escape from shock will be quicker, and that the amygdala is necessary for the reorganization of foraging patterns [45**]. These shock-induced changes in the foraging pattern are consistent with the risk allocation hypothesis.…”
Section: The Emergence Of Neuroethological Approaches To Survival Cirsupporting
confidence: 62%
See 1 more Smart Citation
“…Helmstetter and Fanselow [44] found that introduction of random shocks caused rats to decrease meal frequency but increase meal size such that they reduce exposure to footshocks in the foraging area while maintaining caloric intake. A recent study showed that random footshocks also caused rats to decrease pressing the lever distal to the nest, where it will take the animal longer to escape from shock, and increase pressing the lever proximal to the nest, where escape from shock will be quicker, and that the amygdala is necessary for the reorganization of foraging patterns [45**]. These shock-induced changes in the foraging pattern are consistent with the risk allocation hypothesis.…”
Section: The Emergence Of Neuroethological Approaches To Survival Cirsupporting
confidence: 62%
“…The main advantage of using a robotic predator is that it allows reliable and quantitative interaction with the rat, which is not possible with real predatory animals, such as a cat. The fleeing behavior can be elicited reliably in naïve rats simply by stimulating their amygdala or dorsal PAG each time they approached the food[45**]. In contrast to rats that faced the predatory robot, however, with amygdala/PAG stimulation the animals were unable to procure food placed near the nest, presumably because the brain stimulation evoked the same magnitude of fear regardless of the nest-food distance.…”
Section: The Emergence Of Neuroethological Approaches To Survival Cirmentioning
confidence: 99%
“…This hunger/aversive behavior tradeoff has been noted in rodents in semi-naturalistic foraging environments (12) and has been described for a specialized subset of hypothalamic neurons (13). By this logic, high levels of acyl-ghrelin, which under some circumstances can promote hunger (14), may also facilitate exploration to increase the opportunity to find food.…”
Section: Resultsmentioning
confidence: 88%
“…Critically, although the dose of the ghrelin receptor agonist used here can exacerbate food consumption following acute food deprivation (Figure S3D), it did not stimulate hunger in the memory consolidation period following fear conditioning (Figure 3C; Figure S3E), during which rats were not food deprived. This is important because overt hunger could interfere with fear memory formation in a number of ways that are not directly related to the consolidation of associative fear memory, including the promotion of food-seeking behaviors that compete with freezing (12, 23), or the bias of attention away from fear cues and towards the detection of food (24). Our data reveal that enhanced ghrelin signaling decreases fear memory strength in the absence of possible confounds of hunger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation